(untitled) - Moravcik, Lubomir (Doprava a spoje, 2010)
It is indisputable that world oil supplies are running out. For currently used fuels of motor vehicles (petrol and diesel oil) is important to find alternative propulsions. The future alternative transport fuel has to offer attractiveness for favourable price.